Teacher’s Creative Materials to Enhance Students in the English Classes - Carrera , Sully; Barón, Azael (CIEX JOURNAL, 2025)
This research aims to delve into educational creativity by examining the diverse variety of materials used by teachers to foster an enriched classroom environment. This study investigates how teachers could utilize creative materials to stimulate student engagement, facilitate active learning, and cultivate a dynamic educational experience. Through an analysis of teacher practices and student responses, this research uncovers the role of creative materials in promoting critical thinking, problem-solving skills, and intrinsic motivation among students. Findings reveal the significance of teachers’ creativity in crafting stimulating learning environments that foster curiosity, exploration, and deep understanding.